Environmental Modelling with GIS and Remote Sensing - Skidmore, Andrew (CRC Press, 2009)
Most government agencies and private companies are investing significant resources in the production and use of geographical data. The capabilities of Geographical Information Systems (GIS) for data analysis are also improving, to the extent that the potential performance of GIS software and the data available for analysis outstrip the abilities of managers and analysts to use and analyze the information. This is especially true for environmental applications. Here the need to keep up-to-date is essential for providing effective and efficient services.